A Case of spinal cord decompression sickness: Diagnostic dilemmas and barriers to hyperbaric therapy in Indonesia - Nugroho, Suryanto Eko Agung; Triyuliarto, Dwiwardoyo; Arlando, Choga Ilham; Putra, Rico Wicaksana (Faculty of Medicine, Universitas Islam Indonesia, 2025)
The majority of dives go off without any problems, but there are physiological changes brought on by pressure fluctuations in the underwater environment that might cause serious harm. Decompression sickness (DCS) is a condition resulting from the formation of nitrogen bubbles in body tissues due to rapid decompression after a dive, and one of the severe manifestations of DCS is spinal cord DCS. Although it is uncommon, it is a neurological diving emergency that can cause permanent impairment. The gold standard treatment for all DCS, including spinal cord DCS, is hyperbaric oxygen (HBO) therapy. In this article, we present a case report of a 43-year-old male with spinal cord DCS with a high MEDSUBHYP score, but who refused HBO therapy, which led to long-term morbidity and residual neurological deficits. The patient had received non-steroidal anti-inflammatory drugs (NSAIDs) and methylprednisolone as adjunctive therapy, but they provided no benefit. This article discusses the clinical presentation of spinal cord DCS, its challenging diagnosis, and several factors that predicted poor prognosis in patients with spinal cord DCS. We also highlight the logistical barrier to getting HBO therapy in Indonesia, which may be one of the main reasons the patient refused to be referred to another facility.